The nurse's performance in the care of oncopediatric patients (Research, Society and Development, 2023)
Introduction: Childhood cancer was considered an acute disease with a poor prognosis. Currently, it has a high possibility of cure, with a potential increase in survival. Oncology Nursing is part of the multidisciplinary team, it is up to professionals to establish a helping relationship with the patient and family, through effective communication, humanizing care, promoting symptom control, measures for pain relief and psychological comfort, the professionals should seek to provide patients with biopsychosocial well-being throughout the treatment. Objective: to identify the actions carried out by nurses aimed at comprehensive care for children undergoing cancer treatment. Results: The importance of family support during treatment, as well as the child's coexistence with it and respect for the feelings and beliefs that the professional needs to have, in relation to the patient and his family. The inclusion of the family in the treatment was seen as a positive factor, although nurses still have difficulties in dealing with it. It was possible to analyze that the nurse working in the oncopediatric ward needs to have personal characteristics that make him be there, in addition to his professional skills, to know how to deal with the pain of patients and their families, the scientific knowledge to perform tests and administer medications, the nurse must be prepared to manage his own feelings. Conclusion: It is up to nurses the arduous task of managing not only the technical attributions of nursing, but the personal feelings, of patients and their families, thus it can be observed that caring for children in oncology is complex and can cause a lot of suffering to the team.